Epithelial NAD+ depletion drives mitochondrial dysfunction and contributes to intestinal inflammation - Novak, Elizabeth A.; Crawford, Erin C.; Mentrup, Heather L.; Griffith, Brian D.; Fletcher, David M.; Flanagan, Meredith R.; Schneider, Corinne; Firek, Brian; Rogers, Matthew B.; Morowitz, Michael J.; Piganelli, Jon D.; Wang, Qian; et al. (Frontiers in Immunology, 2023)
Mitochondrial dysfunction has been demonstrated to drive disease progression in inflammatory bowel disease (IBD). We have previously demonstrated that a pathologic downregulation of peroxisome proliferator-activated receptor-gamma coactivator 1-alpha (PGC1a) within the intestinal epithelium contributes to the pathogenesis of IBD. However, the mechanism underlying downregulation of PGC1α expression and activity during IBD is not yet clear. Herein, we demonstrate a significant depletion in the NAD + levels within the intestinal epithelium of mice undergoing experimental colitis, as well as humans with ulcerative colitis. While we found no decrease in the levels of NAD +synthesizing enzymes within the intestinal epithelium of mice undergoing experimental colitis, we did find an increase in the mRNA level, as well as the enzymatic activity, of the NAD + -consuming enzyme poly(ADP-ribose) polymerase-1 (PARP1). Treatment of mice undergoing experimental colitis with an NAD + precursor reduced the severity of colitis, restored mitochondrial function, and increased active PGC1α levels; however, NAD + repletion did not benefit transgenic mice that lack PGC1α within the intestinal epithelium, suggesting that the therapeutic effects require an intact PGC1α axis. These findings emphasize the importance of PGC1α expression to not only mitochondrial health, but also homeostasis within the intestinal epithelium and suggest a novel therapeutic approach for disease management.